Analysis of profitability, liquidity, solvency, company size, independent commissioners, and their effect on tax avoidance (empirical study of manufacturing companies listed on the indonesia stock exchange in 2019-2023): Tax Avoidance - Riri Magdalena, Silvia Cahaya Oktaria; Haryanti, Widi; Harjito, Yunus (Institute of Computer Science (IOCS), 2025)
This research is conducted to examine the influence of profitability, liquidity, solvency, firm size, and the presence of independent commissioners on tax avoidance within manufacturing companies subject to the Indonesia Stock Exchange (IDX) amid 2019 to 2023. Quantitative approach is adopted in this study, utilizing secondary data as the primary source of information. Data processing and statistical analysis are done by the SPSS version 21 software. The research population comprises 226 manufacturing firms registered on the IDX throughout the five-year span. Using a purposive sampling technique, a total of 345 data points were gathered from a selected sample of 69 companies. The study utilizes multiple linear regression analysis to interpret given data. Findings reveal that solvency significantly impacts tax avoidance, whereas profitability, liquidity, size of the company, including the amount of independent commissioners show no significant influence to the tax avoidance practices.